2017
DOI: 10.1103/physrevlett.119.266803
|View full text |Cite
|
Sign up to set email alerts
|

Charge Catastrophe and Dielectric Breakdown During Exposure of Organic Thin Films to Low-Energy Electron Radiation

Abstract: The effects of exposure to ionizing radiation are central in many areas of science and technology, including medicine and biology. Absorption of UV and soft-x-ray photons releases photoelectrons, followed by a cascade of lower energy secondary electrons with energies down to 0 eV. While these low energy electrons give rise to most chemical and physical changes, their interactions with soft materials are not well studied or understood. Here, we use a low energy electron microscope to expose thin organic resist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…The new reactive state of the molecule can be a result of scission of the carbon–hydrogen bond and the subsequent removal of a hydrogen atom from the molecule, charge reorganization after electron attachment, or an energetically excited state after detachment of the electron. The increased resistance toward damage at very low electron energies is in contrast to results from similar LEEM experiments on PMMA and the molecular organometallic EUV resist known as tin-oxo cage; , for both, it was found that electrons with energies all the way down to 0 eV (with respect to vacuum energy) can cause chemical changes in the resist layer. Lower susceptibility of aromatic organic molecules toward irradiation damage, compared to their derivatives which contain also single bonds, such as the case of pentacene and bis­(triisopropylsilylethynyl) pentacene, , or compared to saturated molecules, has already been reported in various studies.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…The new reactive state of the molecule can be a result of scission of the carbon–hydrogen bond and the subsequent removal of a hydrogen atom from the molecule, charge reorganization after electron attachment, or an energetically excited state after detachment of the electron. The increased resistance toward damage at very low electron energies is in contrast to results from similar LEEM experiments on PMMA and the molecular organometallic EUV resist known as tin-oxo cage; , for both, it was found that electrons with energies all the way down to 0 eV (with respect to vacuum energy) can cause chemical changes in the resist layer. Lower susceptibility of aromatic organic molecules toward irradiation damage, compared to their derivatives which contain also single bonds, such as the case of pentacene and bis­(triisopropylsilylethynyl) pentacene, , or compared to saturated molecules, has already been reported in various studies.…”
Section: Discussioncontrasting
confidence: 77%
“…Knowledge of the role of secondary electrons, which generally have low energies, is also of great importance to understand and improve extreme ultraviolet (EUV) lithography, generally considered the key lithographic technology for the next decade(s). 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way chemical yield can be obtained as function of the electron energy. Since the low energy electrons are injected in the resist from outside, the interpretation of electron-matter interaction and the ongoing reactions is much more complex especially for very low energies 1-10eV [17], however, this kind of measurements seem in particular interesting to determine the electron activation energy for a reaction, i.e. the minimum electron energy required to observe a significant reaction response [15].…”
Section: Low Energy Electron Induced Chemical Yieldmentioning
confidence: 99%